Surface Modification Of Tungsten Carbide Cobalt By Electrical Discharge Coating With Quarry Dust Suspension - Liew, Pay Jun; Yap, Ching Yee; Jiwang, Yan (Springer Nature, 2020)
This study explores the feasibility of reusing waste quarry dust as a coating material for surface modification of tungsten carbide cobalt (WC-Co) using electrical discharge coating (EDC). The main objective is to investigate the effect of quarry dust suspension with different concentrations (0–40 g/l) on the characteristics of coated surface such as coating layer thickness, coating element composition and chemical compound, surface morphology, surface roughness and Vickers micro-hardness. Before the EDC process, characterisation of the raw quarry dust was conducted through scanning electron microscopy, X-ray fluorescence and particle size analyser. The results showed that the coating layer thickness was strongly affected by the quarry dust concentration. The formation of hard carbides (SiC, Mg2C3, Fe2C and CaC2) and oxide phases (SiO2, Al2O3, Fe2O3, CaO, CoO and ZnO) in the coated layer due to material migration was confirmed through X-ray diffraction analysis. Vickers micro-hardness of the coated surface was improved significantly with the addition of quarry dust. The best surface finish without micropores and microcracks was obtained using a quarry dust concentration of 10 g/l. These results demonstrated the capability of recycling quarry dust as an environmentally friendly coating material for surface modification